Chapter Parole pesanti. Hate Speech e comunicazione politica ai tempi dei social media - Belluati, Marianna (Studi e saggi, 2021)
The process of increased connectivity has made the issue of "hate speech" more and more relevant in the social and political debate. The effects of hate speech and its viral diffusion on most social media are producing deteriorating effects in the contemporary social and political environments, with direct consequences on the quality of the democratic debate and on the level of institutional respect. The chapter suggests that an ethical approach based on values can be much more effective than sanctions and regulations in the contrast to hate speech practices.